Pulmonary recovery from COVID-19 in patients with metabolic diseases: a longitudinal prospective cohort study - Thomas Sonnweber; Philipp Grubwieser; Alex Pizzini; Anna Boehm; Sabina Sahanic; Anna Luger; Christoph Schwabl; Gerlig Widmann; Alexander Egger; Gregor Hoermann; Ewald Wöll; Bernhard Puchner; et al. (Scientific Reports, 2023)
Abstract The severity of coronavirus disease 2019 (COVID-19) is related to the presence of comorbidities including metabolic diseases. We herein present data from the longitudinal prospective CovILD trial, and investigate the recovery from COVID-19 in individuals with dysglycemia and dyslipidemia. A total of 145 COVID-19 patients were prospectively followed and a comprehensive clinical, laboratory and imaging assessment was performed at 60, 100, 180, and 360 days after the onset of COVID-19. The severity of acute COVID-19 and outcome at early post-acute follow-up were significantly related to the presence of dysglycemia and dyslipidemia. Still, at long-term follow-up, metabolic disorders were not associated with an adverse pulmonary outcome, as reflected by a good recovery of structural lung abnormalities in both, patients with and without metabolic diseases. To conclude, dyslipidemia and dysglycemia are associated with a more severe course of acute COVID-19 as well as delayed early recovery but do not impair long-term pulmonary recovery.